Redesain Website Menggunakan Metode User Centered Design Untuk Meningkatkan Pengalaman Calon Siswa Merpati Training Center - Azzah Oktavian Kuncahyo; Valentinus Roby Hananto; Sri Hariani Eko Wulandari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Merpati Training Center is a certified educational institution that focuses on the aviation industry with 5 course departments in it. MTC has a website to expand information about events, promotions, education costs, facilities and online registration. However, based on initial interviews and questionnaires, SUS found problems, namely that the menu was not well organized, it was not possible to carry out online transactions, and the initial SUS results showed a value of 50.1 which was included in the grade scale F. In order to improve the quality of management of the MTC website, the The solution is to redesign the UI/UX of the MTC website using User Centered Design. The results of this research were in the form of a prototype which was implemented on the website which was then re-evaluated using SUS and obtained a result of 81.5 and was included in the “acceptable” category and the “excellent” rating, which means the appearance of the MTC website is better, acceptable and makes it easier for users.